The Genocide Debate - Beachler, D. author. aut Link
X, 202 p.
Keywords: Neither a case study of a particular genocide nor a work of comparative genocide, this book explores the political constraints and imperatives that motivate debates about genocide in the academic world and, to a lesser extent, in the political arena. The book is an analysis of the ways that political interests shape discourse about genocide.